2021
DOI: 10.31234/osf.io/9gdqr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural priming persists for (at least) one month in young adults, but not in healthy older adults

Abstract: Implicit learning theories suggest that we update syntactic knowledge based on prior experience (e.g., (Chang et al., 2006). To determine the limits of the extent to which implicit learning can influence syntactic processing, we investigated whether structural priming effects persist up to one month post-exposure, and whether they persist less long in healthy older (compared to younger) adults. We conducted a longitudinal experiment with three sessions: Session A, session B (one week after A), and session C (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…After exposure to seven instances of a causative structure, however, they produced active transitive sentences only 30% of the time. Given that the cumulative priming effect is assumed to reflect the operation of an implicit learning mechanism (e.g., Jaeger & Snider, 2013) and that structural priming persists over four weeks for young adult speakers (Heyselaar & Segaert, 2021), the results may suggest that structural priming could facilitate L2 development by promoting L2 learners' acquisition of and access to the abstract syntactic representation of an L2 structure through implicit learning.…”
Section: Discussionmentioning
confidence: 93%
“…After exposure to seven instances of a causative structure, however, they produced active transitive sentences only 30% of the time. Given that the cumulative priming effect is assumed to reflect the operation of an implicit learning mechanism (e.g., Jaeger & Snider, 2013) and that structural priming persists over four weeks for young adult speakers (Heyselaar & Segaert, 2021), the results may suggest that structural priming could facilitate L2 development by promoting L2 learners' acquisition of and access to the abstract syntactic representation of an L2 structure through implicit learning.…”
Section: Discussionmentioning
confidence: 93%
“…To further investigate whether structural priming can serve as a learning mechanism for L2 speakers, it would be interesting to examine whether the priming of Dutch subject RCs among English L1 speakers could also lead to the correct production of this structure. Furthermore, research on within-structural priming in L1 production has shown that the effects of structural priming can persist for as long as a week (Kaschak et al, 2011) or in some speakers even for a month (Heyselaar & Segaert, 2021). To gauge the potential implications and possibilities for educational practices in the field of L2 acquisition, more research is needed to investigate how long structural priming effects persist in L2 learners.…”
Section: Discussionmentioning
confidence: 99%